2007
DOI: 10.1002/pssa.200723137
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of ZnO nanorods for evanescent field optical sensors

Abstract: The optical wave guiding properties of ZnO nanorods are simulated and studied in detail using a block‐iterative frequency‐domain method and the results of a finite difference method as reference data. The simulations are performed for different wavelengths in the infrared spectral region that are related to specific gas absorption lines. Here both single ZnO nanorods and nanorod arrays with varying period lengths are investigated. The evanescent field distributions and penetration depths into the surrounding m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…In theoretical simulations based on MIT Photonic Bands (MPB) program and Finite Difference Method (FDM), the penetration depth of the evanescent field around a hexagonal ZnO NR with a diameter of 500 nm was predicted as approximately 125 nm when excitation of 761 nm was used. 91 Figure 7 summarizes these simulation results on the evanescent field of ZnO NR. The outcomes corroborate with the observation of a relatively large decay length of fluorescence enhancement (much longer than 100 nm) in ZnO NR biodetection systems.…”
Section: Properties Of Zno Nrs Used In Enhanced Fluorescence Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In theoretical simulations based on MIT Photonic Bands (MPB) program and Finite Difference Method (FDM), the penetration depth of the evanescent field around a hexagonal ZnO NR with a diameter of 500 nm was predicted as approximately 125 nm when excitation of 761 nm was used. 91 Figure 7 summarizes these simulation results on the evanescent field of ZnO NR. The outcomes corroborate with the observation of a relatively large decay length of fluorescence enhancement (much longer than 100 nm) in ZnO NR biodetection systems.…”
Section: Properties Of Zno Nrs Used In Enhanced Fluorescence Detectionmentioning
confidence: 99%
“…Reprinted with permission from Ref. #91, S. Börner, C. E. Rüter, T. Voss, D. Kip, and W. Schade, Phys. Stat.…”
Section: Figurementioning
confidence: 99%
“…1D subwavelength waveguides not only carry a larger fraction of their modal power outside the core compared to conventional optical fibers, but also enhance the evanescent wave field and its penetration depth. The penetration depth of an evanescent field around a hexagonal ZnO NR, predicted by theoretical simulations based on the MIT Photonic-Bands program and finite-difference method, is approximately 125 nm for a NR of 500 nm in diameter for 761-nm light (77). Figure 4 c displays 2D finite-difference time-domain (FDTD) calculation results of the electric field ( E ) of a light pulse emitted from a NR by varying the NR diameter ( d ) from 300 nm to 1 µm while considering E within the NR cavity as well as outside as a surface evanescent wave.…”
Section: Biomedically Relevant Optical Properties Of Zno Nanorodsmentioning
confidence: 99%
“…( e ) Penetration depth ( d p ) obtained by the MIT Photonic-Bands (MPB) program and the finite-difference method (FDM) as a function of diameter for λ = 761 nm. Panels c, d , and e adapted from Reference 77 with permission. Copyright 2007 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Figurementioning
confidence: 99%
“…Light can produce various optical and optoelectronic responses from the materials and, therefore, light-matter interactions can be engineered to produce desirable optical properties such as spontaneous and stimulated emission, 1,25-29 waveguiding, 1-3 and evanescence field enhancement. 4,[30][31][32] Such examples can be seen in the research efforts previously reported for the development of SO nanomaterials for applications in nanoscale lasers, 25,26,29 subwavelength waveguides, 1-3,33,34 and biodetection platforms. 17,18,20,23,24,33,35 Specifically, nanomaterials of zinc oxide (ZnO), tin oxide (SnO 2 ), indium tin oxide (ITO), and zinc tin oxide (ZTO) have been widely utilized as signal transduction elements in optical detection devices.…”
mentioning
confidence: 99%